A Dynamic Theory of Secession - Joan Esteban; Sabine Flamand; Massimo Morelli; Dominic Rohner (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper builds a dynamic theory of secessions, conflictual or peaceful, analyzing the forward looking interaction between groups in a country. The proposed framework allows us to jointly address several key stylized facts on secession, and generates several novel predictions. We find that if a group out of power is small enough, then the group in power can always maintain peace with an acceptable offer of surplus sharing for every period, while when there is a mismatch between the relative size and the relative surplus contribution of the minority group, conflict followed by secession can occur. Accepted peaceful secession is predicted for large groups of similar prosperity, and higher patience is associated to a higher chance of secession. We formulate as a result a number of policy recommendations on various dimensions of federalism and other institutions.
Keywords: C70; D74; 330; secessions; conflict; surplus sharing; mismatch